An experimental and theoretical study on an injection-assisted air-conditioner using R32 in the refrigeration cycle. (1st January 2017) - Qv, Dehu; Dong, Bingbing; Cao, Lin; Ni, Long; Wang, Jijin; Shang, Runxin; Yao, Yang
Highlights: An advanced injection-assisted air-conditioner (IAC) using R32 was proposed. In the whole day-night cycle, cooling capacity and energy efficiency ratio of the IAC were enhanced dramatically. The injection duration of 8 s maximized the IAC cooling potential. Two-phase injection attained the highest exergetic efficiency approximating 50% or more. The economic and environmental benefits of the IAC were demonstrated. Abstract: An air-conditioner (AC) that uses refrigerant R32 assisted with one-phase vapor injection shows high energy efficiency and low discharge temperature in the heat-pump cycle, but the performance is not satisfactory in the refrigeration cycle. In this study, an improved injection cycle consisting of one-phase vapor injection mode and two-phase injection mode is proposed and integrated into an AC using R32, which is now referred to as an advanced injection-assisted air-conditioner (IAC). Through an experimental and theoretical study, an optimal injection duration of 8 s is attained for maximizing the refrigeration potential of the IAC. Furthermore, in an entire day–night cycle, both the cooling capacity and energy efficiency ratio (EER) of the IAC within the two-phase injection cycle are enhanced by 25% and 32%, respectively, compared with those of a noninjection-assisted AC. Moreover, two-phase injection offers the highest exergetic efficiency, approximately 50% or more in the refrigeration cycle, exhibiting remarkable thermodynamic performance of the IAC. In addition, compared to the conventional AC using R410A, the IAC using R32 within a two-phase injection cycle demonstrates reasonable payback performance and substantial reduction in carbon dioxide and sulfur dioxide emissions in the refrigeration cycle.